Guidance Note for Surveillance Under Article IV Consultations. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2015)
This note provides country teams with guidance on bilateral and multilateral surveillance in the context of Article IV consultations. It covers the following issues: Focus on stability. Stability is the organizing principle of surveillance. Article IV consultations should focus on the conduct of economic and financial policies pursued by members to promote present and prospective domestic and balance of payments stability, as well as global economic and financial stability. For the latter, Article IV consultations should discuss spillovers from members' economic and financial policies that may significantly affect global stability, including alternative policy options that would minimize their adverse impact. Operational guidance. The note provides detailed guidance, suggestions and references in areas covered in surveillance including risks and spillovers, fiscal policy, macrofinancial and monetary policy, BOP stability, structural policies and data issues. Communication and Engagement. Effective two-way communication is key to surveillance, including with the authorities (to help staff's advice get traction), the Executive Board (to support effective peer review), and the public and other stakeholders (to gain support for necessary policy adjustments). Surveillance messages need to be clear, concise, and focused. The Fund needs to be evenhanded, in line with the principle of uniformity of treatment, for surveillance to command the confidence of the membership. Process and formal requirements. A number of procedures, rules, and requirements are summarized in this note.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet